Phenotypic expansion illuminates multilocus pathogenic variation. (December 2018) - Karaca, Ender; Posey, Jennifer; Coban Akdemir, Zeynep; Pehlivan, Davut; Harel, Tamar; Jhangiani, Shalini; Bayram, Yavuz; Song, Xiaofei; Bahrambeigi, Vahid; Yuregir, Ozge Ozalp; Bozdogan, Sevcan; Yesil, Gozde; et al.
Abstract Purpose Multilocus variation—pathogenic variants in two or more disease genes—can potentially explain the underlying genetic basis for apparent phenotypic expansion in cases for which the observed clinical features extend beyond those reported in association with a "known" disease gene. Methods Analyses focused on 106 patients, 19 for whom apparent phenotypic expansion was previously attributed to variation at known disease genes. We performed a retrospective computational reanalysis of whole-exome sequencing data using stringent Variant Call File filtering criteria to determine whether molecular diagnoses involving additional disease loci might explain the observed expanded phenotypes. Results Multilocus variation was identified in 31.6% (6/19) of families with phenotypic expansion and 2.3% (2/87) without phenotypic expansion. Intrafamilial clinical variability within two families was explained by multilocus variation identified in the more severely affected sibling. Conclusion Our findings underscore the role of multiple rare variants at different loci in the etiology of genetically and clinically heterogeneous cohorts. Intrafamilial phenotypic and genotypic variability allowed a dissection of genotype–phenotype relationships in two families. Our data emphasize the critical role of the clinician in diagnostic genomic analyses and demonstrate that apparent phenotypic expansion may represent blended phenotypes resulting from pathogenic variation at more than one locus.